2011
DOI: 10.2152/jmi.58.227
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of severe stroke patients: Is the ADL status at discharge from a stroke center indicative of the long-term outcome?

Abstract: The objective of this study was to examine the possibility of predicting the long-term outcome of severe stroke patients from the ADL status at discharge. The design is a retrospective observational study in the stroke center at Tokushima University Hospital. Severe stroke patients at discharge with Barthel Index (BI) scores ≤ 40 (N=51) were divided into two subgroups retrospectively, improved and unimproved. The Functional Independence Measure (FIM) and BI were analyzed at discharge, 3 and 6 months after onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…It was found that even in the case of those with the same disability type, the influence on obesity rate varies, depending on the extent of restrictions on physical and dietary activities as well as differences in energy metabolism in accordance with grade of disability. In the case of people with severe disabilities, they tend to exert more energy during physical activities due to activity impairment caused by combinations of problems in vision, hearing, and static sense, and have difficulties in eating due to lowered cognitive function and a weakened state of consciousness [22-24]. In other words, people with severe disability show low obesity rates because of decreased calorie intake due to restrictions on physical activities and increased consumption of energy during physical activities.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that even in the case of those with the same disability type, the influence on obesity rate varies, depending on the extent of restrictions on physical and dietary activities as well as differences in energy metabolism in accordance with grade of disability. In the case of people with severe disabilities, they tend to exert more energy during physical activities due to activity impairment caused by combinations of problems in vision, hearing, and static sense, and have difficulties in eating due to lowered cognitive function and a weakened state of consciousness [22-24]. In other words, people with severe disability show low obesity rates because of decreased calorie intake due to restrictions on physical activities and increased consumption of energy during physical activities.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke is a common cause of impaired mobility and disability in daily activity [13]. Rehabilitation after stroke usually is a prolonged or even lifelong undertaking for the survivors [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many inpatient rehabilitation hospitals have raised their admission FIM requirements, such that people with severe impairments have limited access to dedicated stroke care units and remain on general recovery units where therapy intensity remains low, 6 despite evidence that improvements on the motor FIM are possible months later. 7,8…”
Section: Introductionmentioning
confidence: 99%
“…Many inpatient rehabilitation hospitals have raised their admission FIM requirements, such that people with severe impairments have limited access to dedicated stroke care units and remain on general recovery units where therapy intensity remains low, 6 despite evidence that improvements on the motor FIM are possible months later. 7,8 Very little is known about the capacity for physiological recovery in people with severe impairments after stroke. Many studies exclude people with severe stroke; for example, brain imaging research often excludes people who have sustained a severe stroke, though when severe stroke patients are imaged, physiological improvements can be demonstrated.…”
Section: Introductionmentioning
confidence: 99%